Potassium-magnesium citrate versus potassium chloride in thiazide-induced hypokalemia - Wuermser, Lisa-Ann; Reilly, Christopher; Poindexter, John R.; Sakhaee, Khashayar; Pak, Charles Y.C. (Kidney international, 2000)
Potassium-magnesium citrate versus potassium chloride in thiazide-induced hypokalemia. The purpose of this study was to compare the value of potassium-magnesium citrate (KMgCit) with potassium chloride in overcoming thiazide-induced hypokalemia. Sixty normal subjects first took hydrochlorothiazide (HCTZ; 50 mg/day). After three weeks of treatment (or earlier if hypokalemia developed), they were randomized to take KMgCit (42 mEq K, 21 mEq Mg, and 63 mEq citrate/day) or potassium chloride (42 mEq/day) for three weeks while continuing on HCTZ. KMgCit significantly increased the serum potassium concentration from 3.42 ± 0.30 mEq/L on HCTZ alone to about 3.8 mEq/L (P < 0.001). Potassium chloride produced a similar increase in serum potassium concentration from 3.45 ± 0.44 mEq/L to about 3.8 mEq/L (P < 0.001). KMgCit significantly increased the serum magnesium concentration by 0.11 to 0.12 mEq/L (P < 0.01), whereas potassium chloride produced a marginal decline or no significant change. KMgCit was less effective than potassium chloride in correcting HCTZ-induced hypochloridemia and hyperbicarbonatemia. KMgCit, but not potassium chloride, significantly increased urinarypH (by about 0.6 unit), citrate (by about 260 mg/day), and urinary magnesium. KMgCit is equally effective as potassium chloride in correcting thiazide-induced hypokalemia. In addition, KMgCit, but not potassium chloride, produces a small but significant increase in serum magnesium concentration by delivering a magnesium load, and it confers alkalinizing and citraturic actions.